Apakah Leverage Menjadi Pedang Bermata Dua Bagi Kinerja Keuangan di Tengah Kondisi Financial Distress ? - Nesa Delfi Eftasari; Neny Desriani (Jurnal Mutiara Ilmu Akuntansi, 2025)
This article aims to review the literature related to the role of financial distress risk in the relationship between leverage and a company's financial performance. Although leverage is often used to support expansion and increase profits, its presence also has the potential to increase the risk of financial distress which can have a negative impact on the company's financial performance. This study uses a literature review approach, which involves the process of identifying, assessing, and interpreting evidence from previous studies to answer existing research questions. Overall, effective financial distress risk management can have a positive impact on the stability of a company's financial performance. However, challenges related to leverage management remain a major concern. Therefore, further research is needed to identify optimal strategies that companies can implement in mitigating financial distress risk and improving financial performance. Keywords: , ,